The theory of event coding (TEC) as embodied-cognition framework - Hommel, Bernhard (Frontiers in Psychology, 2015)
The concept of embodied cognition attracts enormous interest but neither is the concept particularly well-defined nor is the related research guided by systematic theorizing. To improve this situation the Theory of Event Coding (TEC) is suggested as a suitable theoretical framework for theorizing about cognitive embodiment—which however presupposes giving up the anti-cognitivistic attitude inherent in many embodiment approaches. The article discusses the embodiment-related potential of TEC, and the way and degree to which it addresses Wilson’s (2002) six meanings of the embodiment concept. In particular, it is discussed how TEC considers human cognition to be situated, distributed, and body-based, how it deals with time pressure, how it delegates work to the environment, and in which sense it subserves action.